2013
DOI: 10.1093/cercor/bht283
|View full text |Cite
|
Sign up to set email alerts
|

Neural Conflict-Control Mechanisms Improve Memory for Target Stimuli

Abstract: According to conflict-monitoring models, conflict serves as an internal signal for reinforcing top-down attention to task-relevant information. While evidence based on measures of ongoing task performance supports this idea, implications for long-term consequences, that is, memory, have not been tested yet. Here, we evaluated the prediction that conflict-triggered attentional enhancement of target-stimulus processing should be associated with superior subsequent memory for those stimuli. By combining functiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

27
99
7

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(138 citation statements)
references
References 49 publications
27
99
7
Order By: Relevance
“…Furthermore, in line with other recent studies (Krebs et al, 2013;Rosner et al, 2014), recognition memory was better for hard-selection than for easy-selection items. As such, the present results converge with others indicating that …”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Furthermore, in line with other recent studies (Krebs et al, 2013;Rosner et al, 2014), recognition memory was better for hard-selection than for easy-selection items. As such, the present results converge with others indicating that …”
Section: Discussionsupporting
confidence: 92%
“…The purpose of the present study was to determine whether recently demonstrated effects of congruency on remembering (Krebs et al, 2013;Rosner et al, 2014) owe to an increase in cognitive control in response to conflict (e.g., Botvinick et al, 2001), or more straightforwardly to increased time-on-task. Superior recognition for the difficult encoding condition was observed only in Experiment 1, in which blocked presentation of the two selection difficulty conditions maximized the opportunity for differences in cognitive control.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…No other significant between-mood or betweengroup interaction was found. For small volume correction, we used findings from conflict processing literature: two meta-analyses of conflict processing studies: (1) Roberts and Hall (2008) and (2) Nee et al (2007); two recent studies using face-word interference task (without load factor): emotional (3) Chechko et al (2012) and non-emotional (4) Krebs et al (2013); one study of task-induced deactivation during stroop performance: (5) Harrison et al (2011). We also used (6) one meta-analysis from 221 studies with the factor 'Load' by Neurosynth.org (reverse inference, selection of the peak as a function of the Z score), and three meta-analyses of studies in BD patients: (7) …”
Section: Behavioral Responsesmentioning
confidence: 99%